ANALISIS HUKUM TERHADAP PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT DI INDONESIA - David Njotowidjaja (PT. Hasba Edukasi Mandiri, 2025)
This research analyzes the implementation of competition law in Indonesia in addressing monopolistic practices and unfair business competition in the contemporary digital economy era. Employing a normative juridical approach with analysis of Law Number 5 of 1999 and related regulations, this study examines the effectiveness of existing legal frameworks in handling modern business competition challenges. Research findings indicate that Indonesia's competition law regulations face significant limitations in accommodating digital economic developments, particularly in addressing predatory pricing practices through flash sales, abuse of dominant position by e-commerce platforms, and data monopolization. Monopolistic practices have evolved from traditional forms into sophisticated models through corporate group structures with cross-shareholding and interlocking directorates that are difficult to detect. The Business Competition Supervisory Commission (KPPU) encounters limitations in authority, technical capacity, and resources in handling complex digital business competition cases. The COVID-19 pandemic exacerbated the situation with the emergence of more aggressive anti-competitive practices in the online retail sector. This research recommends the need for regulatory modernization, institutional capacity strengthening, and harmonization of competition law with digital technology developments to create a healthy and equitable competitive ecosystem.